Optimization of the extraction of natural phenolic antioxidants from the seeds of Tamarindus indica L. - an undervalued by product of food processing - using response surface methodology - Sarkar, Atreyi; Ghosh, Uma (Acta Biologica Szegediensis, 2018)
The seeds of Tamarindus indica are known to possess a wide range of phenolic compounds with high antioxidant activity as measured by the ferric reducing antioxidant power (FRAP). In the present study, the optimum conditions for the extraction of crude phenolic antioxidants from Tamarind seed were determined using response surface methodology (RSM). A central composite design (CCD) was used to investigate the effects of four independent variables, namely concentration of extractable solids in solvent (g/ml; X1), extraction time (h; X2), extraction temperature (°C; X3) and solvent concentration (%, v/v; X4) on the responses of total polyphenol content (TPC) and FRAP. The CCD consisted of 30 experimental runs. A second-order polynomial model was used for predicting the responses. Canonical analysis of the surface responses revealed that the predicted optimal conditions for the maximal yield of TPC and FRAP were concentration of extractable solids in solvent of 0.049 g/ml, extraction time of 3.24 h, extraction temperature of 45 °C and a solvent concentration of 50%. The experimental values in the optimised condition coincided with the predicted ones within a 95% confidence interval, hence indicating the suitability of the model and the success of RSM in optimizing the extraction parameters.